Nanoparticles boost pomegranate growth and defense, suppressing root-knot nematodes - Abdel-Wahab, Dalia A.; El-Zawahry, Aida M.I.; Hamada, Afaf M.; Abdel-Salam, Maha M.; Samy, Ahmed M. (Frontiers in Plant Science, 2025)
Root-knot nematodes (Meloidogyne spp.) are a major threat to pomegranate cultivation. Nanoparticles (NPs) present a possible substitute nematicide that lessens dependency on potentially dangerous chemical nematicides. This study assessed the efficacy of copper oxide (CuO) and iron oxide (Fe2O3) NPs to promote pomegranate (Punica granatum L. cultivar Hegazy) growth and provide protection against the root-knot nematode (Meloidogyne javanica). The application of the NPs as copper oxide (CuO) and iron oxide (Fe2O3) involved both drenching and spraying using 50 mg/L on one-year-old pomegranate (Punica granatum cultivar Hegazy) seedlings, nematode-infected with (Meloidogyne javanica). By assessing how CuO and Fe2O3 NPs affect nematode and pomegranate growth, and some biochemical traits. Treatments with NPs successfully reduced the number of pomegranate root egg masses, galls, and juvenile nematodes in soil. NP treatments exhibited increased side branching, leaf area, levels of photosynthetic pigments (chlorophyll a, b, and carotenoids), total antioxidants, thiol compounds [glutathione (GSH), non-protein thiols (NPTs), protein thiols (PTs)], and flavonoids. However, NP treatments reduced the accumulation of malondialdehyde (MDA) and proline, stress markers, in pomegranate plants infected with nematodes. NP treatments did not affect the production of phenolic compounds in pomegranates. These results indicate that the NP effect partially depends on the increased production of photosynthetic pigments, thiol compounds, and flavonoids. These results elucidate how nanoparticles control nematode infection. Further research in this area is necessary to determine whether NPs are the best treatment for nematode infections.